A global perspective on private higher education - Shah, Mahsood; Nair, Chenicheri Sid (Chandos Publishing is an imprint of Elsevier, 2016)
AiAGlobal Perspective on Private Higher Education provides a timely review of the significant growth of private higher education in many parts of the world during the last decade. The book is concurrent with significant changes in the external operating environment of private higher education, including government policy and its impact on the ongoing growth of the sector. The title brings together the trends relating to the growth and the decline of private higher education providers, also including the key contributing factors of the changes from 17 countries.